2021
DOI: 10.2147/jpr.s310381
|View full text |Cite
|
Sign up to set email alerts
|

Are Psychotropic Medications Effective in Chronic Pain Management in Children and Adolescents? A Meta-Analysis of Randomized Control Trials

Abstract: Objective Data defining and subsequently guiding the use of psychotropic medications in children and adolescents is sparse. We conducted a meta-analysis of randomized control trials to examine the effectiveness of psychotropic medications in children and adolescents with chronic pain. Methods We conducted a comprehensive literature search from published studies, and annual scientific sessions of psychiatry conferences. We identified double-blind, randomized control tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…In the above cases, significant improvement in mental health symptoms and chronic pain of patients were noted when pharmacological and psychotherapeutic interventions were utilized. In terms of pharmacological management, the evidence of using non-opioid pharmacological agents has been limited mostly to the use of NSAIDs and anticonvulsants, with only recent evidence supporting the use of psychotropic medications, mainly from the antidepressant category [ 10 ]. Antidepressants work through pathways that involve increased norepinephrine and serotonin in the synaptic clefts near the spinal cord that have an inhibitory effect on the perception of pain [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the above cases, significant improvement in mental health symptoms and chronic pain of patients were noted when pharmacological and psychotherapeutic interventions were utilized. In terms of pharmacological management, the evidence of using non-opioid pharmacological agents has been limited mostly to the use of NSAIDs and anticonvulsants, with only recent evidence supporting the use of psychotropic medications, mainly from the antidepressant category [ 10 ]. Antidepressants work through pathways that involve increased norepinephrine and serotonin in the synaptic clefts near the spinal cord that have an inhibitory effect on the perception of pain [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, duloxetine via 5-HT and NA has been found to modulate ascending spinal nociceptive neurotransmission via the descending inhibitory pain pathway, which is why duloxetine is used in chronic pain [ 11 , 12 ]. There have been some recent studies further establishing the role of anti-depressant medications in the treatment of chronic pain conditions in pediatric and adult populations [ 13 ]. There are many medications used to treat complex rheumatological diseases like AOSD, and clinicians should be aware of any drug-drug interactions between immunomodulators and other medications [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Function, based on the Brief Pain Inventory (BPI) Interference score, was also improved, which was inconsistent with the previous findings of no effect of duloxetine on function. Updated metaanalyses with this trial continued to show duloxetine associated with a small improvement in mean pain intensity (4 RCTs, N=1,462, MD -0.54, 95% CI, -0.76 to -0.34, I 2 =0%) 9,[29][30][31] and likelihood of pain response (4 RCTs, N=1,451, 58.3% vs. 47.3%, RR 1.26, 95% CI, 1.13 to 1.39, I 2 =%), 9,[29][30][31] and no effect on function based on the BPI Interference Score (4 RCTs, N=1,437, MD -0.42, 95% CI, -0.77 to -0.14, I 2 =36%). 9,[29][30][31] Two fair-quality RCTs (N=654), added to this update, reported mixed results for pain outcomes with naproxen compared with placebo in low back pain.…”
Section: Low Back Painmentioning
confidence: 92%
“…Updated metaanalyses with this trial continued to show duloxetine associated with a small improvement in mean pain intensity (4 RCTs, N=1,462, MD -0.54, 95% CI, -0.76 to -0.34, I 2 =0%) 9,[29][30][31] and likelihood of pain response (4 RCTs, N=1,451, 58.3% vs. 47.3%, RR 1.26, 95% CI, 1.13 to 1.39, I 2 =%), 9,[29][30][31] and no effect on function based on the BPI Interference Score (4 RCTs, N=1,437, MD -0.42, 95% CI, -0.77 to -0.14, I 2 =36%). 9,[29][30][31] Two fair-quality RCTs (N=654), added to this update, reported mixed results for pain outcomes with naproxen compared with placebo in low back pain. 7,8 One 16-week treatment trial (n=525) found a small but statistically significant reduction in pain intensity with naproxen (MD -0.41, p=0.037) and 30-percent or greater pain response (p=0.009) with baseline observation carried forward for missing data.…”
Section: Low Back Painmentioning
confidence: 92%
See 1 more Smart Citation